2000
DOI: 10.1088/0953-8984/12/49/311
|View full text |Cite
|
Sign up to set email alerts
|

Optical bands related to dislocations in Si

Abstract: First-principles calculations are used to investigate the interaction of self-interstitial aggregates with the 90° partial dislocation in Si. We find that I4 is bound to the line with an energy of around 3 eV. The defect causes deep levels to appear in the band gap and optical transitions between these levels may account for the luminescent bands relating to plastically deformed Si.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…However, in the present case, the size of the models is out of reach of ab-initio techniques, the electronic structure of the ( ) a c + -mixed dislocation was then explored using the SCC-DFTB methodology. Over several applications, the latter method has proven to provide electronic structures qualitatively in agreement with those obtained by more sophisticated ab-initio methods [14,15]. Although we end up with deep and shallow levels in the bandgap for the two core configurations, the calculated electronic structure show some different features (Fig.…”
supporting
confidence: 60%
“…However, in the present case, the size of the models is out of reach of ab-initio techniques, the electronic structure of the ( ) a c + -mixed dislocation was then explored using the SCC-DFTB methodology. Over several applications, the latter method has proven to provide electronic structures qualitatively in agreement with those obtained by more sophisticated ab-initio methods [14,15]. Although we end up with deep and shallow levels in the bandgap for the two core configurations, the calculated electronic structure show some different features (Fig.…”
supporting
confidence: 60%
“…19 This hypothesis is also in agreement with the theoretical anticipation of Blumenau et al, 20 who showed that the isolated tetra selfinterstitial defects in silicon, which present a very shallow acceptor level, should emit in this range of energies. 19 This hypothesis is also in agreement with the theoretical anticipation of Blumenau et al, 20 who showed that the isolated tetra selfinterstitial defects in silicon, which present a very shallow acceptor level, should emit in this range of energies.…”
Section: B Samples Heat Treated At 650°csupporting
confidence: 86%
“…From the first-principle calculations, it was shown that the I 4 defect clusters could bring deep levels in the band gap causing the optical transitions between these levels, which may account for the dislocations related luminescence. 20 Some other studies, such as inducing super saturation of non-equilibrium self-interstitials by ion implantation forming a silicon layer in which compression stresses appeared, also shown the strong D1/D2 luminescence. 34 On the other hand, during the high temperature annealing, oxygen atoms could diffuse quickly and get gathered at dislocations in CZ silicon, 35 which is also confirmed by the FTIR results in our case.…”
Section: -mentioning
confidence: 95%
“…9,10 In fact, four photoluminescence (PL) lines related to dislocations (D1 to D4 lines) were first detected at 4.2 K in 1970s 11,12 and investigated intensively in the last three decades. [13][14][15][16][17][18][19][20][21][22][23][24] However, the radiative-recombination mechanism of excessive carriers at dislocations is still unclear. The major concerns are about the nature of the D1 and D2 lines' luminescence centers and the role of impurities and point defects during the recombination process.…”
Section: Introductionmentioning
confidence: 99%